Changes in the gut microbiome of older adults according to hypertension control - Valdez-Palomares, Fernanda; Texis, Tomas; Sánchez-García, Sergio; Martínez-Ezquerro, José Darío; la Torre, Paola García-de; Rodríguez-Dorantes, Mauricio; Genis-Mendoza, Alma; Fabela, Salvador; Palacios-González, Berenice; González-Covarrubias, Vanessa (Frontiers in Microbiology, 2025)
Hypertension is the leading cause of cardiovascular disease, with over 60% prevalence in older adults, and its control is complex and requires multidisciplinary approaches. The role of the gut microbiome in blood pressure control remains unclear despite reported associations of some specific bacteria involved in the development of hypertension. The aim of this study was to characterize the gut microbiome of older adults and to identify bacteria associated with hypertension control. Patients aged 60 years and older from Mexico City and the metropolitan area, all of whom were receiving antihypertensive treatment, provided a feces sample during a routine medical visit. DNA was extracted from 240 samples using a commercial kit, the V3/V4 region of the 16S gene was sequenced, and metataxonomic analyses were performed using QIIME and R. Bacterial abundance analysis identified a core microbiome in the hypertensive older adults, with an increased abundance of Escherichia-Shigella and a decrease in alpha diversity with increasing age. Ruminococcus UCG-002, DTU 089, and members of the Lachnospiraceae family were distinctively abundant in controlled hypertension. These bacteria are fiber-fermenting and producers of short-chain fatty acids (SCFAs), and their differential abundance according to hypertension control suggests an intricate interplay among SCFA producers. Our results confirm and expand upon previous reports on the core gut microbiome of older adults, suggesting relevant changes in fiber-fermenting bacteria—Ruminococcus UCG-002, DTU 089, and members of the Lachnospiraceae family—for hypertension control.